2015
DOI: 10.1007/s10270-015-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability testing in the wild: the Drupal case study

Abstract: Variability testing techniques search for effective and manageable test suites that lead to the rapid detection of faults in systems with high variability. Evaluating the effectiveness of these techniques in realistic settings is a must, but challenging due to the lack of variability intensive systems with available code, automated tests and fault reports. In this article, we propose using the Drupal framework as a case study to evaluate variability testing techniques. First, we represent the framework variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Functional prioritization objectives are those based on the functional features of the system and their interactions. Some examples are those based on combinatorial interaction testing [75], configuration dissimilarity [2,33,60] or feature model complexity metrics [59,60]. Non-functional prioritization objectives consider extra-functional information such as user preferences [21,39], cost [75], memory consumption [45] or execution probability [15] to find the best ordering for test cases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Functional prioritization objectives are those based on the functional features of the system and their interactions. Some examples are those based on combinatorial interaction testing [75], configuration dissimilarity [2,33,60] or feature model complexity metrics [59,60]. Non-functional prioritization objectives consider extra-functional information such as user preferences [21,39], cost [75], memory consumption [45] or execution probability [15] to find the best ordering for test cases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Non-functional prioritization objectives consider extra-functional information such as user preferences [21,39], cost [75], memory consumption [45] or execution probability [15] to find the best ordering for test cases. In a previous work [59], we performed a preliminary evaluation comparing the effectiveness of several functional and non-functional prioritization objectives in accelerating the detection of faults in an HCS. Results suggested that non-functional properties such as the number of changes or the number of defects in a previous version of the system were among the most effective prioritization criteria.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations